Glass for chemical strengthening and chemically strengthened glass
By using chemically strengthened glass with a specific composition and specialized chemical strengthening treatment, the problem of devitrification in lithium aluminum silicon glass during manufacturing and forming has been solved, achieving chemically strengthened glass with large surface compressive stress and depth, thus improving the strength and safety of the glass.
Patent Information
- Application Number
- CN202511150877.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-02-05
- Filing Date
- 2018-10-03
- Publication Date
- 2025-11-18
AI Technical Summary
Existing lithium aluminum silicon glass is prone to devitrification during manufacturing and forming, making it difficult to simultaneously increase the surface compressive stress value and the compressive stress layer depth, which increases the risk of fragment scattering.
Chemically strengthened glass with a specific composition contains 45%–75% SiO2, 1%–30% Al2O3, 1%–20% Li2O, 0%–5% Y2O3, 0%–5% ZrO2, and 0%–1% TiO2, and contains a total of 1%–20% of any one or more of MgO, CaO, SrO, BaO, and ZnO, with a total of 0%–10% Na2O and K2O, and a total of 0%–10% B2O3 and P2O5, and an M value of 1000 or higher. It achieves a surface compressive stress of 300 MPa or higher by chemical strengthening treatment with sodium nitrate and potassium nitrate at 450°C.
Chemically strengthened glass that is less prone to devitrification has been achieved, with high surface compressive stress values and compressive stress layer depth, which improves the strength and safety of the glass.
Smart Images

Figure CN120965096A_ABST
Abstract
Description
[0001] This application is a divisional application of Chinese Patent Application No. 201880088438.6, filed on October 3, 2018, entitled "Glass for Chemical Strengthening". TECHNICAL FIELD
[0002] The present application relates to a glass for chemical strengthening and a chemically strengthened glass. BACKGROUND
[0003] In recent years, in order to protect and improve the appearance of display devices of mobile devices such as mobile phones, smartphones, portable information terminals (PDA), tablet terminals, and the like, a protective glass containing a chemically strengthened glass has been used.
[0004] In a chemically strengthened glass, the higher the surface compressive stress (value) (CS) and the depth of the compressive stress layer (DOL) are, the higher the strength tends to be. On the other hand, in order to maintain the balance with the surface compressive stress, internal tensile stress (CT) is generated inside the glass, and therefore, the larger the CS and DOL are, the larger the CT is. When a glass with a large CT breaks, it becomes a violent breaking mode in which the number of fragments is large, and the risk of scattering of the fragments increases.
[0005] In Patent Literature 1, it is described that a stress distribution represented by a curved line is formed by two-step chemical strengthening treatment, whereby it is possible to increase the surface compressive stress while suppressing the internal tensile stress. Specifically, a method in which a KNO3 / NaNO3 mixed salt with a low K concentration is used for the first step chemical strengthening, and a KNO3 / NaNO3 mixed salt with a high K concentration is used for the second step chemical strengthening, and the like are proposed.
[0006] In addition, in Patent Literature 2, a lithium aluminum silicon glass having a large surface compressive stress and a depth of the compressive stress layer is disclosed by two-step chemical strengthening treatment. The lithium aluminum silicon glass can simultaneously increase CS and DOL by two-step chemical strengthening treatment using a sodium salt in the first step chemical strengthening treatment and a potassium salt in the second step chemical strengthening treatment.
[0007] PRIOR ART DOCUMENTS
[0008] PATENT LITERATURE
[0009] Patent Literature 1: U.S. Patent Application Publication No. 2015 / 0259244 Specification
[0010] Patent Literature 2: Japanese Patent Application Laid-Open No. 2013-520388 SUMMARY
[0011] PROBLEMS TO BE SOLVED BY THE INVENTION
[0012] Recently, thinner and lighter protective glasses, protective glasses processed into a curved shape, and the like have been increasingly demanded, and lithium-aluminum-silicon glass capable of simultaneously increasing a surface compressive stress value (CS) and a compressive stress depth of layer (DOL) has been attracting attention.
[0013] However, lithium-aluminum-silicon glass has a tendency to easily devitrify in a glass manufacturing process or in a process of bending and shaping the obtained glass.
[0014] An object of the present application is to provide a glass for chemical strengthening that is less likely to devitrify and that can achieve a large CS and a large DOL.
[0015] Means for solving the problem
[0016] The present application provides a glass for chemical strengthening, wherein, in terms of molar percentage on an oxide basis, the glass for chemical strengthening contains:
[0017] 45 to 75% of SiO2, 1 to 30% of Al2O3, 1 to 20% of Li2O, 0 to 5% of Y2O3, 0 to 5% of ZrO2, and 0 to 1% of TiO2, and
[0018] 1 to 20% in total of any one or more of MgO, CaO, SrO, BaO, and ZnO,
[0019] the total content of Na2O and K2O is 0 to 10%,
[0020] the total content of B2O3 and P2O5 is 0 to 10%, and
[0021] an M value represented by the following formula is 1000 or more.
[0022] M = -5 x [SiO2] + 121 x [Al2O3] + 50 x [Li2O] - 35 x [Na2O] + 32 x [K2O] + 85 x [MgO] + 54 x [CaO] - 41 x [SrO] - 4 x [P2O5] + 218 x [Y2O3] + 436 x [ZrO2] - 1180
[0023] Further, provided is a glass for chemical strengthening, wherein a surface compressive stress value after chemical strengthening by immersing the glass for chemical strengthening in sodium nitrate at 450°C for 1 hour reaches 300 MPa or more, and a surface compressive stress after chemical strengthening by immersing the glass for chemical strengthening in sodium nitrate at 450°C for 3 hours and then immersing in potassium nitrate at 450°C for 1.5 hours is 800 MPa or more, and, in terms of molar percentage on an oxide basis, a basic composition of the chemically strengthened glass contains:
[0024] 45 to 75% of Si02, 1 to 30% of Al203, 1 to 20% of Li20, 0 to 5% of Y203, 0 to 5% of Zr02, and 0 to 1% of Ti02, and
[0025] containing 1 to 20% in total of any one or more of MgO, CaO, SrO, BaO, and ZnO,
[0026] the total content of Na20 and K20 is 0 to 10%,
[0027] the total content of B203and P205is 0 to 10%, and
[0028] M represented by the aforementioned formula is 1000 or more.
[0029] Effects of the Invention
[0030] According to the present application, a chemical strengthening glass which is less likely to devitrify and has a large surface compressive stress value (CS) and a large compressive stress layer depth (DOL) can be provided. BRIEF DESCRIPTION OF DRAWINGS
[0031] Figure 1 is a graph showing the relationship between I and the crystal growth rate.
[0032] Figure 2 is a graph showing the relationship between I2and the devitrification property.
[0033] Figure 3 is an example of a graph showing the relationship between the fictive temperature and the refractive index.
[0034] Figure 4 is a schematic view of a platinum container used for the determination of the crystal growth rate.
[0035] Figure 5 is a temperature distribution graph of a float simulation temperature lowering condition. DETAILED DESCRIPTION
[0036] Hereinafter, the chemical strengthening glass according to the present application will be described in detail, but the present application is not limited to the following embodiments, and can be arbitrarily modified and implemented without departing from the gist of the present application.
[0037] In the present specification, "chemical strengthening glass" refers to a glass after chemical strengthening treatment. In addition, "chemical strengthening glass" refers to a glass before chemical strengthening treatment.
[0038] In the present specification, the glass composition of the glass for chemical strengthening is sometimes referred to as the basic composition of the chemically strengthened glass. In the chemically strengthened glass, a compressive stress layer is generally formed in the surface portion of the glass by ion exchange, and thus the glass composition of the portion not subjected to ion exchange coincides with the basic composition of the chemically strengthened glass.
[0039] In the present specification, the glass composition is expressed in terms of molar percentage on an oxide basis, and the molar % is sometimes abbreviated as %. In addition, "~" indicating a numerical range is used in the meaning that the numerals recited before and after it are included as the lower limit value and the upper limit value.
[0040] "Substantially not containing" in the glass composition means not containing, i.e., not intentionally containing, except for unavoidable impurities contained in raw materials and the like. Specifically, for example, the content in the glass composition is less than 0.1 mol%.
[0041] In the present specification, "stress distribution" means a graph in which the compressive stress value is represented with the depth from the glass surface as the variable. A negative compressive stress value indicates tensile stress.
[0042] In the present specification, the "frangibility" of the glass means the property that the fragments easily scatter when the glass is broken.
[0043] Hereinafter, unless otherwise specified, the "surface compressive stress value" of the glass is the surface compressive stress value when a glass sheet having a thickness of 0.8 mm is subjected to chemical strengthening treatment after being kept at a temperature 50°C higher than the glass transition temperature Tg for 1 hour or more and then slowly cooled at a cooling rate of 0.5°C / minute. The surface compressive stress generated by the chemical strengthening treatment has a tendency to be greater as the fictive temperature of the glass is lower, and the fictive temperature of the glass is affected by the heat history (e.g., the cooling rate) to which the glass is subjected. The evaluation is performed by eliminating the effect of the fictive temperature through heat treatment and slow cooling.
[0044] In addition, the "β-OH value" is calculated from the transmittance X1 (%) at a reference wavelength of 4000 cm -1 nearby, which is the absorption wavelength of the hydroxyl group, the minimum transmittance X2 (%) in the vicinity of 3570 cm -1 of the glass sheet (unit: mm), according to Equation (1).
[0045] β-OH value = (1 / t) log 10 (X1 / X2) ··· (1)
[0046] Note that the β-OH value can be adjusted by the amount of moisture contained in the glass raw material or the melting conditions.
[0047] <GLASS FOR CHEMICAL STRENGTHENING>
[0048] The chemical strengthening glass of the present application (hereinafter sometimes referred to as "the present glass") contains, in terms of molar percentage on an oxide basis:
[0049] 45 to 75% of SiO2,
[0050] 1 to 30% of Al2O3,
[0051] 1 to 20% of Li2O,
[0052] 0 to 5% of Y2O3,
[0053] 0 to 5% of ZrO2, and
[0054] 0 to 1% of TiO2, and
[0055] contains 1 to 20% in total of any one or more of MgO, CaO, SrO, BaO and ZnO,
[0056] the total content of Na2O and K2O is 0 to 10%,
[0057] the total content of B2O3 and P2O5 is 0 to 10%.
[0058] The present glass, in addition to satisfying the aforementioned composition range, has a value M represented by the following formula of 1000 or more.
[0059] M = -5 x [SiO2] + 121 x [Al2O3] + 50 x [Li2O] - 35 x [Na2O] + 32 x [K2O] + 85 x [MgO] + 54 x [CaO] - 41 x [SrO] - 4 x [P2O5] + 218 x [Y2O3] + 436 x [ZrO2] - 1180
[0060] In the formula, [SiO2], [Al2O3], [Li2O], [Na2O], [K2O], [MgO], [CaO], [SrO], [P2O5], [Y2O3] and [ZrO2] represent the content of each component in terms of molar percentage. The same applies hereinafter.
[0061] The present inventors and others have studied the relationship between the glass composition of a chemical strengthening glass and the compressive stress value that can be introduced by chemical strengthening treatment, and the relationship with the chemical strengthening characteristics, and found that a glass having a large value of the aforementioned M has a large compressive stress value that can be introduced by chemical strengthening treatment, and is less likely to produce devitrification (crystallization).
[0062] The present inventors and others have studied surface compressive stress when chemical strengthening treatment is performed and crystal growth rate at 850°C to 1200°C with respect to various glass compositions. As the chemical strengthening treatment conditions, a case where strengthening is performed by immersion in sodium nitrate at 450°C for 1 hour (one-step strengthening treatment) and a case where chemical strengthening is performed by immersion in sodium nitrate at 450°C for 3 hours and then immersion in potassium nitrate at 450°C for 1.5 hours (two-step strengthening treatment) were evaluated.
[0063] As a result, in a glass having an M value of 1000 or more, the surface compressive stress (CS1) after one-step strengthening treatment by immersion in sodium nitrate at 450°C for 1 hour reached 300 MPa or more. In addition, the surface compressive stress (CS2) after two-step strengthening treatment by immersion in sodium nitrate at 450°C for 3 hours and then immersion in potassium nitrate at 450°C for 1.5 hours reached 800 MPa or more.
[0064] It was also confirmed that a glass having a large M value has a small crystal growth rate at 850°C to 1200°C and has a tendency to suppress the generation of defects due to devitrification at the time of glass production. The evaluation method of the crystal growth rate will be described later.
[0065] The M value is more preferably 1100 or more and further preferably 1200 or more. However, in the case where the M value is excessively large, the glass can become brittle, and thus it is preferably 1800 or less, more preferably 1650 or less, further preferably 1500 or less, and typically 1350 or less.
[0066] In addition, the present glass, in addition to satisfying the aforementioned composition range, has an I value represented by the following formula, which is preferably 850 or less and more preferably 600 or less.
[0067] I = 4.8 x [Si02] + 102 x [Al203] + 81 x [Li20] - 272 x [Na20] - 281 x [K20] - 16 x [MgO] - 25 x [Y203] + 0.028 x [Zr02] + 63
[0068] The present inventors and others have studied the glass composition and devitrification characteristics of a glass for chemical strengthening and found that the aforementioned I value has a high correlation with the crystal growth rate at 700°C to 1200°C of the glass described later.
[0069] Figure 1 is a graph plotting the I value and the crystal growth rate of the glasses of the Examples and Comparative Examples described later.
[0070] The I value is preferably 850 or less, further preferably 600 or less, and does not easily cause devitrification during glass production. The I value is more preferably 500 or less, still more preferably 400 or less, particularly preferably 300 or less, and most preferably 200 or less. The lower limit of the I value is not particularly limited, and is preferably greater than 50, more preferably 80 or more, and particularly preferably 100 or more, in consideration of the compressive stress value generated by chemical strengthening of the glass.
[0071] The present inventors have also found that the I2 value represented by the following formula is preferably 5 or less in addition to the aforementioned composition range.
[0072] I2= 0.27 x [SiO2] + 1.4 x [Al2O3] - 1.1 x [Na2O] - 1.7 x [K2O] + 0.38 x [MgO] - 1.36 x [Y2O3] - 0.59 x [ZrO2] - 23
[0073] The present inventors have studied the glass composition and devitrification characteristics of a glass for chemical strengthening, and have found that if the glass composition is one in which the aforementioned I2 value is small, then devitrification does not easily occur when the glass is cooled from a temperature above the liquidus temperature.
[0074] The present inventors have produced glasses (A1 to A18) having the compositions shown in Tables 1 and 2, and have performed two-step heat treatment in which the glass is held at 1300°C for 30 minutes and then held at the temperature shown in the second step treatment temperature column (850°C to 1200°C) for 10 minutes, and have observed whether or not devitrification occurs. In Tables 1 and 2, the presence or absence of devitrification and the number of temperature conditions in which devitrification occurs are described for each second step treatment temperature. In the tables, "N" indicates that no devitrification was observed, and "•" indicates that devitrification was observed. For example, in the case of the glass of A3, devitrification was observed at two conditions, 850°C and 900°C, and thus the number of temperature conditions in which devitrification occurs is 2. A glass in which the number of temperature conditions in which devitrification occurs in the two-step heat treatment is small has a low probability of devitrification when cooling is performed from a high temperature, and can be said to have good devitrification resistance.
[0075]
[0076]
[0077] The I2 value is preferably 5 or less because devitrification does not easily occur during melting. The I2 value is more preferably 4 or less, further preferably 3 or less, particularly preferably 2 or less, and most preferably 1 or less. The lower limit of the I2 value is not particularly limited, but is preferably greater than -5, more preferably -3 or more, and particularly preferably -1 or more, in consideration of the brittleness of the glass.
[0078] Also, the results of observation of the presence or absence of high-temperature devitrification in the case where cooling was performed under conditions simulating the cooling conditions in the case of manufacturing a glass sheet by the float method (hereinafter referred to as "float simulation cooling conditions") are shown in Tables 1 and 2. Figure 2 The results of these devitrification tests were plotted against the I2 values. From this graph, it was found that the glass having a small I2 value was less likely to be devitrified when formed into a glass sheet by the float method. In particular, the glass having an I2 value of 5 or less was less likely to be devitrified.
[0079] According to the float simulation cooling conditions, the average cooling rate from 1200°C to 600°C was about 15°C / min. In the aforementioned two-step treatment test, the glass in which the number of temperature conditions in which devitrification occurred was large also exhibited devitrification in this test.
[0080] Note that the glass preferably satisfies the aforementioned composition range, and at least one of the M value, the I value, and the I2 value satisfies the aforementioned range, and it is also preferable that two or all three of the values satisfy the aforementioned range.
[0081] Next, the preferred glass composition will be described.
[0082] SiO2is a component that constitutes the skeleton of the glass. In addition, SiO2is a component that improves chemical durability, and SiO2is a component that reduces the generation of cracks when a scratch is generated on the surface of the glass.
[0083] The content of SiO2is preferably 45% or more. The content of SiO2is more preferably 55% or more, further preferably 60% or more, particularly preferably 63% or more, and typically 65% or more. On the other hand, from the viewpoint of improving the meltability, the content of SiO2is 75% or less, preferably 72% or less, further preferably 70% or less, and particularly preferably 68% or less.
[0084] Al2O3is an effective component from the viewpoint of improving the ion exchange performance at the time of chemical strengthening and increasing the surface compressive stress after strengthening.
[0085] The content of Al2O3is preferably 1% or more. Al2O3is a component that increases the glass transition temperature and a component that increases the Young's modulus. The content of Al2O3is preferably 8% or more, more preferably 9% or more, further preferably 10% or more, particularly preferably 11% or more, and typically 12% or more. On the other hand, when the content of Al2O3is too large, the crystal growth rate increases, and the problem of a decrease in yield due to devitrification defects becomes large. In addition, the viscosity of the glass increases, and the meltability decreases. The content of Al2O3is 30% or less, preferably 20% or less, more preferably 18% or less, further preferably 16% or less, and typically 14% or less.
[0086] Li2O is a component that forms surface compressive stress by ion exchange and is a component that improves the melting property of the glass. By containing Li2O in the chemically strengthened glass, a stress profile having a large surface compressive stress and a large compressive stress layer is obtained by a method in which Li ions on the surface of the glass are ion exchanged for Na ions and the Na ions are further ion exchanged for K ions. From the viewpoint of easily obtaining a preferred stress profile, the content of Li2O is preferably 1% or more, more preferably 5% or more, further preferably 7% or more, particularly preferably 9% or more, and typically 10% or more.
[0087] On the other hand, when the content of Li2O is too much, the crystal growth rate during melting of the glass increases, and the problem of reduction in yield due to devitrification defects becomes large. The content of Li2O is preferably 20% or less, more preferably 15% or less, further preferably 13% or less, and typically 12% or less.
[0088] Na2O and K2O are not essential components, but are components that improve the melting property of the glass and reduce the crystal growth rate of the glass, and Na2O and K2O can be added in order to improve the ion exchange performance.
[0089] Na2O is a component that forms a surface compressive stress layer in chemical strengthening treatment using a potassium salt, and in addition, Na2O is a component that can improve the melting property of the glass.
[0090] In order to obtain this effect, the content of Na2O is preferably 1% or more, more preferably 2% or more, further preferably 3% or more, particularly preferably 4% or more, and typically 5% or more. On the other hand, from the viewpoint of avoiding reduction in surface compressive stress (CS) in strengthening treatment due to sodium salt, the content of Na2O is preferably 10% or less, more preferably 8% or less, further preferably 6% or less, and particularly preferably 5% or less.
[0091] K2O can be contained in order to improve the ion exchange performance and the like. In the case where K2O is contained, the content of K2O is preferably 0.5% or more, more preferably 1% or more, further preferably 1.5% or more, particularly preferably 2% or more, and typically 3% or more. On the other hand, from the viewpoint of avoiding reduction in surface compressive stress (CS) due to potassium salt, the content of K2O is preferably 10% or less, more preferably 5% or less, further preferably 3% or less, and particularly preferably 2% or less.
[0092] The total of the contents of Na2O and K2O ([Na2O] + [K2O]) is preferably 0% to 10%, more preferably 5% or more, and further preferably 6% or more. On the other hand, more preferably 8% or less, and particularly preferably 7% or less.
[0093] From the viewpoint of reducing the rate of increase in devitrification, [Li2O] / ([Na2O] + [K2O]) is preferably 3 or less, more preferably 2.5 or less, and further preferably 2 or less. On the other hand, from the viewpoint of increasing the surface compressive stress in the chemical strengthening treatment using sodium, [Li2O] / ([Na2O] + [K2O]) is preferably 0.5 or more, more preferably 0.9 or more, and further preferably 1.3 or more.
[0094] In addition, from the viewpoint of reducing the rate of increase in devitrification, ([Al2O3] + [Li2O]) / ([Na2O] + [K2O] + [MgO] + [CaO] + [SrO] + [BaO] + [ZnO] + [ZrO2] + [Y2O3]) is preferably 4 or less, more preferably 3 or less, and further preferably 2 or less. From the viewpoint of increasing the surface compressive stress in the chemical strengthening treatment using sodium, ([Al2O3] + [Li2O]) / ([Na2O] + [K2O] + [MgO] + [CaO] + [SrO] + [BaO] + [ZnO] + [ZrO2] + [Y2O3]) is preferably 0.5 or more, more preferably 0.7 or more, further preferably 0.9 or more, and particularly preferably 1 or more.
[0095] MgO, CaO, SrO, BaO, and ZnO are not essential components, but any one or more of them is preferably contained from the viewpoint of improving the stability of the glass. The total content of these components, [MgO] + [CaO] + [SrO] + [BaO] + [ZnO], is preferably 1% or more, more preferably 2% or more, further preferably 3% or more, and particularly preferably 4% or more. On the other hand, from the viewpoint of improving the ion exchange ability by chemical strengthening, the total content of these components is preferably 20% or less, more preferably 15% or less, further preferably 10% or less, and still further preferably 8% or less.
[0096] In the case where MgO and one or more of CaO, SrO, BaO, and ZnO are contained, from the viewpoint of reducing the surface reflectance of the glass, [MgO] / ([CaO] + [SrO] + [BaO] + [ZnO]) is preferably 10 or more, more preferably 15 or more, further preferably 20 or more, and particularly preferably 25 or more. This is because CaO, SrO, BaO, and ZnO increase the refractive index as compared with MgO. From the viewpoint of reducing the devitrification temperature, [MgO] / ([CaO] + [SrO] + [BaO] + [ZnO]) is preferably 60 or less, more preferably 55 or less, further preferably 50 or less, and particularly preferably 45 or less.
[0097] From the viewpoint of increasing the meltability of the chemically strengthened glass while reducing the crystal growth rate, it is preferable to contain MgO. The content of MgO is preferably 1% or more, more preferably 2% or more, further preferably 3% or more, particularly preferably 4% or more, and typically 5% or more. On the other hand, when the content of MgO is excessive, it is difficult to increase the compressive stress layer at the time of chemical strengthening treatment. The content of MgO is preferably 15% or less, more preferably 10% or less, further preferably 8% or less, and particularly preferably 6% or less.
[0098] CaO is a component that increases the meltability of the chemically strengthened glass, and CaO can be contained. When CaO is contained, the content of CaO is preferably 0.1% or more, more preferably 0.15% or more, and further preferably 0.5% or more. On the other hand, when the content of CaO is excessive, it is difficult to increase the compressive stress value at the time of chemical strengthening treatment. The content of CaO is preferably 5% or less, more preferably 3% or less, further preferably 1% or less, and typically 0.5% or less.
[0099] SrO is a component that increases the meltability of the chemically strengthened glass, and SrO can be contained. When SrO is contained, the content of SrO is preferably 0.1% or more, more preferably 0.15% or more, and further preferably 0.5% or more. On the other hand, when the content of SrO is excessive, it is difficult to increase the compressive stress value at the time of chemical strengthening treatment. The content of SrO is preferably 3% or less, more preferably 2% or less, further preferably 1% or less, and typically 0.5% or less.
[0100] BaO is a component that increases the meltability of the chemically strengthened glass, and BaO can be contained. When BaO is contained, the content of BaO is preferably 0.1% or more, more preferably 0.15% or more, and further preferably 0.5% or more. On the other hand, when the content of BaO is excessive, it is difficult to increase the compressive stress value at the time of chemical strengthening treatment. The content of BaO is preferably 3% or less, more preferably 2% or less, further preferably 1% or less, and typically 0.5% or less.
[0101] ZnO is a component that increases the meltability of the chemically strengthened glass, and ZnO can be contained. When ZnO is contained, the content of ZnO is preferably 0.1% or more, more preferably 0.15% or more, and further preferably 0.5% or more. On the other hand, when the content of ZnO is excessive, it is difficult to increase the compressive stress value at the time of chemical strengthening treatment. The content of ZnO is preferably 3% or less, more preferably 2% or less, further preferably 1% or less, and typically 0.5% or less.
[0102] ZrO2may not be contained, but from the viewpoint of increasing the surface compressive stress of the chemically strengthened glass, it is preferable to contain ZrO2. The content of ZrO2is preferably 0.1% or more, more preferably 0.2% or more, further preferably 0.5% or more, particularly preferably 0.8% or more, and typically 1% or more. On the other hand, when the content of ZrO2is too much, it is difficult to increase the compressive stress value at the time of chemical strengthening treatment. The content of ZrO2is preferably 5% or less, more preferably 3% or less, further preferably 2% or less, and particularly preferably 1.5% or less.
[0103] TiO2is a component that suppresses solarization of the glass, and TiO2may be contained. When TiO2is contained, the content of TiO2is preferably 0.02% or more, more preferably 0.05% or more, further preferably 0.1% or more, particularly preferably 0.12% or more, and typically 0.15% or more. On the other hand, when the content of TiO2is more than 1%, devitrification easily occurs, and the quality of the chemically strengthened glass can be reduced. The content of TiO2is preferably 1% or less, more preferably 0.5% or less, and further preferably 0.25% or less.
[0104] Y2O3may not be contained, but since Y2O3is a component that increases the surface compressive stress of the chemically strengthened glass while reducing the crystal growth rate, it is preferable to contain Y2O3. The content of Y2O3is preferably 0.1% or more, more preferably 0.2% or more, further preferably 0.5% or more, particularly preferably 0.8% or more, and typically 1% or more. On the other hand, when the content of Y2O3is too much, it is difficult to increase the compressive stress layer at the time of chemical strengthening treatment. The content of Y2O3is preferably 5% or less, more preferably 3% or less, further preferably 2% or less, and particularly preferably 1.5% or less.
[0105] B2O3is not an essential component, but in order to reduce the brittleness of the glass, improve the chipping resistance, and further improve the melting property of the glass, B2O3may be contained. When B2O3is contained, the content of B2O3is preferably 0.5% or more, more preferably 1% or more, and further preferably 2% or more. On the other hand, when the content of B2O3is too much, the acid resistance easily deteriorates, and thus it is preferable to be 10% or less. The content of B2O3is more preferably 6% or less, further preferably 4% or less, and typically 2% or less. From the viewpoint of preventing the occurrence of a wave at the time of melting, it is more preferable to substantially not contain B2O3.
[0106] P2O5 is not an essential component, but can be contained in order to increase the compressive stress layer at the time of chemical strengthening. In the case where P2O5 is contained, the content of P2O5 is preferably 0.5% or more, more preferably 1% or more, and further preferably 2% or more. On the other hand, from the viewpoint of improving acid resistance, the content of P2O5 is preferably 6% or less, more preferably 4% or less, and further preferably 2% or less. From the viewpoint of preventing the generation of a wave at the time of melting, it is more preferable that P2O5 is substantially not contained.
[0107] The total content of B2O3 and P2O5 is preferably 0% to 10%, more preferably 1% or more, and further preferably 2% or more as a lower limit. In addition, the total content of B2O3 and P2O5 is more preferably 6% or less, and further preferably 4% or less.
[0108] La2O3, Nb2O5, Ta2O5, and Gd2O3 are components that reduce the crystal growth rate of the glass and improve the melting property, and La2O3, Nb2O5, Ta2O5, and Gd2O3 can be contained. In the case where these components are contained, the content of each is preferably 0.1% or more, more preferably 0.2% or more, further preferably 0.5% or more, particularly preferably 0.8% or more, and typically 1% or more. On the other hand, when the content of each is too large, it is difficult to increase the compressive stress value at the time of chemical strengthening treatment, and thus the content of each is preferably 3% or less, more preferably 2% or less, further preferably 1% or less, and particularly preferably 0.5% or less.
[0109] Fe2O3 absorbs a heat ray, and thus has an effect of improving the melting property of the glass. In the case where a large melting furnace is used to mass-produce the glass, it is preferable to contain Fe2O3. In this case, the content of Fe2O3 is preferably 0.002% or more, more preferably 0.005% or more, further preferably 0.007% or more, and particularly preferably 0.01% or more, in terms of % by weight on an oxide basis. On the other hand, when Fe2O3 is contained in excess, coloring occurs, and thus from the viewpoint of improving the transparency of the glass, the content of Fe2O3 is preferably 0.3% or less, more preferably 0.04% or less, further preferably 0.025% or less, and particularly preferably 0.015% or less, in terms of % by weight on an oxide basis.
[0110] Note that, here, the iron oxide in the glass is described as being entirely in the form of Fe2O3, but in reality, both Fe(III) in the oxidized state and Fe(II) in the reduced state are mixed. Among these, Fe(III) causes yellow coloring, and Fe(II) causes blue coloring, and in the balance between the two, green coloring occurs in the glass.
[0111] Further, a coloring component can be added within a range that does not hinder achievement of desired chemical strengthening characteristics. As the coloring component, for example, Co3O4, MnO2, NiO, CuO, Cr2O3, V2O5, Bi2O3, SeO2, CeO2, Er2O3, Nd2O3, and the like can be listed as appropriate coloring components.
[0112] The content of the coloring component is preferably 5% or less in terms of mole percentage on an oxide basis. When greater than 5%, the glass sometimes easily devitrifies. The content of the coloring component is preferably 3% or less, and further preferably 1% or less. In the case where it is desired to increase the transmittance of the glass, it is preferable that these components be substantially not contained.
[0113] SO3, chlorides, fluorides, and the like can be appropriately contained as fining agents at the time of melting the glass. It is preferable that As2O3 not be contained. In the case where Sb2O3 is contained, it is preferable that it be 0.3% or less, more preferably 0.1% or less, and most preferably that Sb2O3 not be contained.
[0114] The β-OH value of the present glass is preferably 0.1 mm -1 More preferably, 0.15 mm -1 Further preferably, 0.2 mm -1 Particularly preferably, 0.22 mm -1 Most preferably, 0.25 mm -1 or more.
[0115] A glass having a large β-OH value, which is an index of the water content in the glass, has a tendency to have a lowered softening point and to easily undergo bending processing. On the other hand, from the viewpoint of increasing the strength by chemical strengthening of the glass, when the β-OH value of the glass is large, the value of the surface compressive stress (CS) after the chemical strengthening treatment becomes small, and it is difficult to increase the strength. Therefore, the β-OH value is preferably 0.5 mm -1 More preferably, 0.4 mm -1 Further preferably, 0.3 mm -1 or more.
[0116] In order to increase the shatterability of the glass, the Young's modulus of the present glass is preferably 80 GPa or more, more preferably 82 GPa or more, further preferably 84 GPa or more, and particularly preferably 85 GPa or more. The upper limit of the Young's modulus is not particularly limited, and a glass having a high Young's modulus has a case where the acid resistance is reduced, and therefore the Young's modulus is, for example, 110 GPa or less, preferably 100 GPa or less, and more preferably 90 GPa or less. The Young's modulus can be measured, for example, by the ultrasonic pulse method.
[0117] From the viewpoint of reducing the weight of the product, the density of the present glass is preferably 3.0 g / cm 3The preferred value is 2.8 g / cm³. 3 The following is a further preferred value: 2.6 g / cm³ 3 The following is particularly preferred: 2.55 g / cm³ 3 The following is a general rule regarding the lower limit of density. Glass with low density tends to have lower acid resistance, etc., therefore, a density of, for example, 2.3 g / cm³ is acceptable. 3 The above, preferably 2.4 g / cm³ 3 The above, especially preferred, is 2.45 g / cm³. 3 above.
[0118] From the viewpoint of reducing surface reflection of visible light, the refractive index of this glass is preferably 1.6 or less, more preferably 1.58 or less, even more preferably 1.56 or less, and particularly preferably 1.54 or less. There is no particular limitation on the lower limit of the refractive index. Glass with a low refractive index tends to have low acid resistance; therefore, it is, for example, 1.5 or more, preferably 1.51 or more, and more preferably 1.52 or more.
[0119] From the viewpoint of reducing optical strain, the photoelastic constant of this glass is preferably 33 nm / cm / MPa or less, more preferably 32 nm / cm / MPa or less, even more preferably 31 nm / cm / MPa or less, and particularly preferably 30 nm / cm / MPa or less. Furthermore, glasses with low photoelastic constants tend to have low acid resistance; therefore, the photoelastic constant of this glass is, for example, 24 nm / cm / MPa or more, more preferably 25 nm / cm / MPa or more, and even more preferably 26 nm / cm / MPa or more.
[0120] From the viewpoint of reducing warping after chemical strengthening, the average linear coefficient of thermal expansion (coefficient of thermal expansion) of this glass from 50℃ to 350℃ is preferably 95×10⁻⁶. -7 Below / ℃, more preferably 90×10 -7 Below / ℃, 88×10 is further preferred. -7 Below / ℃, 86×10 is particularly preferred. -7 Below / ℃, the optimal value is 84×10. -7 Below / ℃. There is no particular limit to the lower limit of the coefficient of thermal expansion. Glasses with low coefficients of thermal expansion are sometimes difficult to melt; therefore, the average linear coefficient of thermal expansion (coefficient of thermal expansion) of this glass from 50℃ to 350℃ is, for example, 60 × 10⁻⁶. -7 / ℃ or above, preferably 70×10 -7 / ℃ or higher, more preferably 74×10 -7 / ℃ or higher, more preferably 76×10 -7 / ℃ or above.
[0121] From the viewpoint of reducing the warpage after chemical strengthening, the glass transition temperature (Tg) is preferably 500°C or higher, more preferably 520°C or higher, further preferably 540°C or higher. From the viewpoint of easily performing the float process, it is preferably 750°C or lower, more preferably 700°C or lower, further preferably 650°C or lower, particularly preferably 600°C or lower, most preferably 580°C or lower.
[0122] The temperature at which the viscosity reaches 10 2 dPa • s (T2) is preferably 1750°C or lower, more preferably 1700°C or lower, particularly preferably 1650°C or lower, typically 1600°C or lower. The temperature (T2) is a standard temperature as a melting temperature of the glass, and there is a tendency that the lower T2 is, the easier the glass is to manufacture. The lower limit of T2 is not particularly limited, and a glass with a low T2 sometimes lacks stability, and therefore T2 is usually 1400°C or higher, preferably 1450°C or higher.
[0123] In addition, the temperature at which the viscosity reaches 10 4 dPa • s (T4) is preferably 1350°C or lower, more preferably 1250°C or lower, further preferably 1200°C or lower, particularly preferably 1150°C or lower. The temperature (T4) is a standard temperature as a temperature for forming the glass into a sheet, and there is a tendency that a glass with a high T4 increases the load on the forming equipment. The lower limit of T4 is not particularly limited, and a glass with a low T4 sometimes lacks stability of the glass, and therefore T4 is usually 900°C or higher, preferably 950°C or higher, more preferably 1000°C or higher.
[0124] The devitrification temperature of the present glass is preferably a temperature 120°C or lower than the temperature at which the viscosity reaches 10 4 dPa • s (T4). When the devitrification temperature is higher than T4, devitrification is likely to occur during the forming by the float process, and therefore it is preferable. The devitrification temperature is more preferably a temperature 100°C or lower than T4, further preferably a temperature 50°C or lower than T4, particularly preferably T4 or lower.
[0125] The crystal growth rate of the present glass at 850°C to 1200°C is preferably 600 μm / hour or lower, more preferably 500 μm / hour or lower, further preferably 400 μm / hour or lower, particularly preferably 300 μm / hour or lower. In addition, it is preferable that the maximum crystal growth rate at 700°C to 1200°C be 600 μm / hour or lower.
[0126] In addition, the crystal growth rate of the present glass at 950°C is preferably 600 μm / hour or lower, more preferably 500 μm / hour or lower, further preferably 400 μm / hour or lower, particularly preferably 300 μm / hour or lower.
[0127] In addition, the glass preferably does not devitrify when cooled under the aforementioned float simulation cooling conditions.
[0128] The softening point of the glass is preferably 850°C or lower, more preferably 820°C or lower, and further preferably 790°C or lower. The lower the softening point of the glass, the lower the heat treatment temperature during bending and forming, the smaller the energy consumption, and the smaller the load on the equipment. The lower the softening point, the more preferable from the viewpoint of lowering the bending and forming temperature, but is 700°C or higher in a typical chemically strengthened glass. A glass having a softening point that is too low has a tendency to easily relax the stress introduced during the chemical strengthening treatment and easily become low in strength, and thus the softening point is preferably 700°C or higher. More preferably, the softening point is 720°C or higher, and further preferably 740°C or higher.
[0129] The softening point can be measured by the fiber elongation method described in JIS R 3103-1:2001.
[0130] The glass preferably has a crystallization peak temperature that is higher than the softening point, as measured by the following measurement method. In addition, more preferably, no crystallization peak is observed.
[0131] That is, about 70 mg of the glass is pulverized, ground in an agate mortar, a temperature increase rate of 10°C / minute is set, and measurement is performed using a differential scanning calorimeter (DSC) from room temperature to 1000°C.
[0132] The surface compressive stress value (CS1) in the case where the glass is chemically strengthened by immersion in 450°C sodium nitrate for 1 hour is preferably 300 MPa or higher, more preferably 350 MPa or higher, and further preferably 400 MPa or higher. The larger the CS1, the more preferable from the viewpoint of increasing the strength, and from the viewpoint of suppressing strengthening cracks during the chemical strengthening treatment process, the CS1 is preferably, for example, 800 MPa or lower, more preferably 600 MPa or lower, and further preferably 500 MPa or lower.
[0133] In addition, the compressive stress layer depth (DOL1) in this case is preferably 70 μm or higher, more preferably 80 μm or higher, further preferably 90 μm or higher, and particularly preferably 100 μm or higher. On the other hand, the upper limit of the DOL1 is not particularly limited, and in consideration of the case where the yield of finished products is reduced due to strengthening cracks during the chemical strengthening treatment process, the DOL1 is preferably, for example, 200 μm or lower, more preferably 150 μm or lower, further preferably 130 μm or lower, and particularly preferably 120 μm or lower.
[0134] Note that CS1 and DOL1 can be measured using a scattered light photoelastic stress meter (e.g., manufactured by Kojima Manufacturing Co., Ltd., SLP-1000). In addition, measurement can be performed using a birefringence imaging system Abrio-IM manufactured by Tokyo Instruments Co., Ltd. in accordance with the following procedure.
[0135] A cross section of a chemically strengthened glass having a size of 10 mm x 10 mm or more and a thickness of about 0.2 mm to about 2 mm was polished to a range of 150 μm to 250 μm to be thinned. For the sample thus thinned to about 200 μm to about 1 mm, measurement was performed using a monochromatic light having a wavelength of 546 nm as a light source by transmission light, and the phase difference (retardation) possessed by the chemically strengthened glass was measured using a birefringence imaging system. The stress was calculated from the obtained value and the following equation (2).
[0136] 1.28 x F = δ / (C x t')... Equation (2)
[0137] In equation (2), F is the stress [unit: MPa], δ is the phase difference [unit: nm], C is the photoelastic constant [unit: nm / cm / MPa], and t' is the thickness of the sample [unit: cm].
[0138] The surface compressive stress value CS2 generated by the Na-K ion exchange layer in the case where the present glass is chemically strengthened by immersion in sodium nitrate at 450°C for 3 hours and then immersion in potassium nitrate at 450°C for 1.5 hours is preferably 800 MPa or greater, more preferably 850 MPa or greater, further preferably 900 MPa or greater, particularly preferably 950 MPa or greater, and further 1000 MPa or greater. On the other hand, the upper limit of CS2 is not particularly limited, but in the case where it is desired to reduce the reduction in yield due to strengthening cracks in the chemical strengthening treatment process as much as possible, it is preferably 1500 MPa or less, more preferably 1300 MPa or less, further preferably 1200 MPa or less, and particularly preferably 1100 MPa or less.
[0139] CS2 and DOL2 can be measured by, for example, a surface stress meter FSM-6000 manufactured by Kojima Manufacturing Co., Ltd.
[0140] In addition, in the case where the present glass is chemically strengthened by immersing in sodium nitrate at 450°C for 3 hours and then immersing in potassium nitrate at 450°C for 1.5 hours, the depth of the compressive stress layer DOL3 generated by the Li-Na exchange layer is preferably 100 μm or greater, more preferably 110 μm or greater, further preferably 120 μm or greater, and particularly preferably 130 μm or greater. On the other hand, the upper limit of DOL3 is not particularly limited, but in consideration of the reduction in yield due to strengthening cracks in the chemical strengthening treatment step, for example, it is preferably 200 μm or less, more preferably 180 μm or less, further preferably 170 μm or less, and particularly preferably 160 μm or less.
[0141] DOL3 can be measured by the aforementioned method using a scattered light photoelastic stress meter (for example, SLP-1000 manufactured by OZ Optics Limited) or a birefringence imaging system Abrio-IM manufactured by Tokyo Instruments Inc.
[0142] From the viewpoint of increasing the surface compressive stress generated by chemical strengthening, the fictive temperature of the present glass is preferably a temperature of 80°C or lower than the glass transition temperature (Tg) (hereinafter, referred to as "Tg + 80°C"), more preferably Tg + 50°C or lower, more preferably Tg + 40°C or lower, further preferably Tg + 30°C or lower, more further preferably Tg + 20°C or lower, and particularly preferably Tg + 10°C or lower.
[0143] In the case where the glass is obtained by melting a glass raw material at a high temperature and cooling, the smaller the cooling rate after melting, the lower the fictive temperature of the glass. Therefore, in order to obtain a glass having a very low fictive temperature, it is necessary to cool slowly for a long time. In the case where the glass is cooled slowly, depending on the glass composition, devitrification in which crystals are precipitated during cooling is easily caused. Therefore, in consideration of the production efficiency of the glass and the suppression of devitrification, the fictive temperature is preferably Tg - 30°C or higher, more preferably Tg - 10°C or higher, and further preferably Tg or higher.
[0144] Note that the fictive temperature of the glass can be experimentally obtained from the refractive index of the glass. In a method in which a glass maintained at a constant temperature is rapidly cooled from that temperature, a plurality of glass pieces having the same glass composition but different fictive temperatures are prepared in advance. The fictive temperatures of these glass pieces are the temperatures maintained before rapid cooling, and therefore by measuring the refractive index of these glass pieces, a standard curve in which the refractive index is plotted against the fictive temperature can be prepared. An example is shown in FIG. 1. Even for a glass for which the cooling rate and the like are unclear, the fictive temperature can be obtained from the standard curve by measuring the refractive index. Figure 3 An example is shown in FIG. 1. Even for a glass for which the cooling rate and the like are unclear, the fictive temperature can be obtained from the standard curve by measuring the refractive index.
[0145] However, the standard curve is different depending on the glass composition, and thus a standard curve prepared using a glass having the same composition as the glass for which the fictive temperature is to be determined is required to be used.
[0146] The fictive temperature of the glass has a tendency to increase if the cooling speed is fast and to decrease if the cooling speed is slow. In addition, the fictive temperature has a tendency to be lower as the surface compressive stress after chemical strengthening is larger.
[0147] The glass for chemical strengthening of the present application can be produced by a general method. For example, raw materials of each component of the glass are prepared, and heating and melting are performed in a glass melting furnace. Then, the glass is homogenized by a known method, formed into a desired shape such as a glass sheet, and slowly cooled.
[0148] As the forming method of the glass sheet, for example, a float method, a press method, a fusion method, and a down-draw method can be exemplified. The float method which is suitable for mass production is particularly preferable. In addition, a continuous forming method other than the float method, for example, the fusion method and the down-draw method are also preferable.
[0149] Then, the formed glass is subjected to grinding and polishing treatment as necessary, and a glass substrate is formed. Note that, in the case where the glass substrate is cut into a prescribed shape and size, or chamfer processing of the glass substrate is performed, it is preferable to perform the cutting and chamfer processing of the glass substrate before the chemical strengthening treatment described later is performed, because a compressive stress layer is formed on the end surface by the chemical strengthening treatment thereafter.
[0150] <Chemically Strengthened Glass>
[0151] The basic composition of the chemically strengthened glass of the present application is the same as the glass composition of the glass for chemical strengthening described above. The chemically strengthened glass of the present application preferably has a surface compressive stress value of 800 MPa or more.
[0152] The chemically strengthened glass of the present application can be produced by performing the chemical strengthening treatment on the obtained glass sheet, and then performing cleaning and drying.
[0153] The chemical strengthening treatment can be performed by a known method. In the chemical strengthening treatment, the glass sheet is contacted with a molten solution of a metal salt (for example, potassium nitrate) containing a metal ion having a large ionic radius (typically, K ion) by immersion or the like, so that a metal ion having a small ionic radius (typically, Na ion, Li ion) in the glass sheet is replaced with a metal ion having a large ionic radius (typically, K ion for Na ion, and Na ion for Li ion).
[0154] The chemical strengthening treatment (ion exchange treatment) is not particularly limited, and can be performed, for example, by immersing the glass sheet in a molten salt such as potassium nitrate heated to 360°C to 600°C for 0.1 hour to 500 hours. Note that the heating temperature of the molten salt is preferably 375°C to 500°C, and the immersion time of the glass sheet in the molten salt is preferably 0.3 hours to 200 hours.
[0155] As the molten salt used for the chemical strengthening treatment, nitrates, sulfates, carbonates, chlorides, and the like can be given. Among these, as the nitrates, lithium nitrate, sodium nitrate, potassium nitrate, cesium nitrate, silver nitrate, and the like can be given. As the sulfates, lithium sulfate, sodium sulfate, potassium sulfate, cesium sulfate, silver sulfate, and the like can be given. As the carbonates, lithium carbonate, sodium carbonate, potassium carbonate, and the like can be given. As the chlorides, lithium chloride, sodium chloride, potassium chloride, cesium chloride, silver chloride, and the like can be given. These molten salts can be used alone or in combination.
[0156] In the present application, the treatment conditions for the chemical strengthening treatment are not particularly limited, and appropriate conditions can be selected in consideration of the properties and composition of the glass, the type of the molten salt, and the surface compressive stress, the compressive stress layer depth, and the like of the chemical strengthening properties desired for the finally obtained chemically strengthened glass.
[0157] Further, in the present application, the chemical strengthening treatment can be performed only once, or the chemical strengthening treatment can be performed multiple times under two or more different conditions (multi-step strengthening). Here, for example, as the first-stage chemical strengthening treatment, the chemical strengthening treatment is performed under conditions in which the DOL is large and the CS is relatively small. Then, as the second-stage chemical strengthening treatment, the chemical strengthening treatment is performed under conditions in which the DOL is small and the CS is relatively high, which makes it possible to increase the CS of the outermost surface of the chemically strengthened glass while suppressing the internal tensile stress area (St), and as a result, to suppress the internal tensile stress (CT) to be low.
[0158] In the case where the chemically strengthening glass of the present application is in a sheet shape (glass sheet), the sheet thickness (t) is not particularly limited, but from the viewpoint of improving the effect of chemical strengthening, for example, it is 2 mm or less, preferably 1.5 mm or less, more preferably 1 mm or less, further preferably 0.9 mm or less, particularly preferably 0.8 mm or less, and most preferably 0.7 mm or less. Further, from the viewpoint of obtaining a sufficient effect of strength improvement by the chemical strengthening treatment, the sheet thickness is, for example, 0.1 mm or more, preferably 0.2 mm or more, more preferably 0.4 mm or more, and further preferably 0.5 mm or more.
[0159] The shape of the glass can be other than a plate shape depending on the product or use to which it is applied, and the like. In addition, the glass plate can have a frame shape in which the thickness of the outer periphery is different, or the like. In addition, the shape of the glass plate is not limited to this, and for example, the two main surfaces can not be parallel to each other, and in addition, all or a part of one or both of the two main surfaces can be curved surfaces. More specifically, the glass plate can be, for example, a flat plate-shaped glass plate having no warping, and in addition, can be a curved glass plate having a curved surface.
[0160] The glass is particularly useful as a protective glass used in mobile devices such as mobile phones, smartphones, portable information terminals (PDA), tablet terminals, and the like. In addition, it is also useful in applications such as a protective glass for display devices such as televisions (TV), personal computers (PC), touch panels, and the like, which are not intended for carrying, a wall surface of an elevator, a wall surface (full screen display) of a building such as a house or a building, a building material such as a window glass, a desk surface, an interior of an automobile or an airplane, and the like, or a protective glass therefor, and a housing having a curved shape other than a plate shape by bending processing or molding.
[0161] [Examples]
[0162] Hereinafter, the present application will be described by way of examples, but the present application is not limited thereto. Examples 25 are comparative examples, and the others are examples. Note that for each of the measurement results in the tables, a blank indicates that the measurement was not performed.
[0163] (Production of chemically strengthened glass)
[0164] Glass plates were produced by platinum crucible melting in a manner such that each glass composition was expressed in terms of the molar percentage of the oxides shown in Tables 3 to 6. A generally used glass raw material such as an oxide, a hydroxide, a carbonate, or a nitrate was appropriately selected, and was weighed so as to reach 1000 g in terms of the glass. Next, the mixed raw material was put into a platinum crucible, and was put into an electric resistance heating type electric furnace at 1500°C to 1700°C, was melted for about 3 hours, was deaerated and homogenized. The obtained molten glass was flowed into a mold material, was held at a temperature of the glass transition temperature + 50°C for 1 hour, and was then cooled to room temperature at a rate of 0.5°C / minute, whereby a glass block was obtained. The obtained glass block was cut, ground, and finally both surfaces were finished to a mirror surface, whereby a plate-shaped glass of 50 mm in length x 50 mm in width x 0.8 mm in plate thickness was obtained.
[0165] The physical properties of the glass were evaluated in the following manner. The results are shown in Tables 3 to 6.
[0166] < Density >
[0167] The density measurement was performed by the immersion weighing method (JIS Z 8807:2012, Method for measuring density and specific gravity of solids). The unit is g / cm3 .
[0168] <Young's modulus>
[0169] For the glass before chemical strengthening, Young's modulus (E) (unit; GPa) was measured by an ultrasonic pulse method (JIS R 1602: 1995).
[0170] <Average linear expansion coefficient and glass transition temperature (Tg)>
[0171] The average linear expansion coefficient (α50-350) (unit; 10 -7 / °C) and the glass transition temperature at a temperature of 50°C to 350°C were measured according to the method of JIS R 3102: 1995 "Test method of average linear expansion coefficient of glass".
[0172] <T2, T4>
[0173] For the glass before chemical strengthening, the temperature T2 at which the viscosity reaches 10 2 dPa-s and the temperature T4 at which the viscosity reaches 10 4 dPa-s were measured by a rotational viscometer (according to ASTM C965-96).
[0174] <DSC peak height>
[0175] The peak height (unit; mcal / sec) was measured by the aforementioned DSC measurement.
[0176] <Crystal growth rate>
[0177] The crystal growth rate was measured according to the following procedure.
[0178] The glass pieces were pulverized in a mortar and classified so as to pass through a 3.35 mm mesh sieve, and the glass particles that did not pass through a 2.36 mm mesh sieve were washed with ion exchange water and dried and used for the test.
[0179] In each of the recesses 2 of an elongated platinum cell (platinum cell 1 for devitrification evaluation) having a plurality of recesses as shown in Figure 4 , 1 glass particle 3 was placed, and the glass particles were heated to the surface thereof to be melted and become smooth at 1000°C to 1100°C in an electric furnace.
[0180] Next, the glass was put into a temperature gradient furnace kept at a prescribed temperature, and heat treatment was performed for a constant time (set to T), and then taken out to room temperature and quenched. According to this method, since the elongated container can be set in the temperature gradient furnace and heat treatment can be performed on a plurality of glass particles at the same time, the maximum crystal growth rate in a prescribed temperature range can be measured.
[0181] The glass after heat treatment was observed using a polarizing microscope (manufactured by Nikon Corporation: ECLIPSE LV100ND), and the diameter of the largest crystal observed in the crystal was measured (set as L μm). The observation was performed under the conditions of an ocular 10 times, an objective lens 5 to 100 times, transmitted light, and polarized light observation. It is considered that the crystal generated by devitrification grows isotropically, and thus the crystal growth rate is L / (2T) [unit: μm / hour].
[0182] However, the crystal to be measured is selected from a crystal that does not precipitate from the interface with the container. This is because the crystal growth at the metal interface has a different tendency from the crystal growth behavior that occurs at the inside of the glass or the glass-atmosphere interface.
[0183] <Devitrification temperature>
[0184] The crushed glass particles were placed in a platinum dish, and heat treatment was performed for 17 hours in an electric furnace controlled to a constant temperature. The glass after heat treatment was observed using a polarizing microscope, and the devitrification temperature was estimated by a method of evaluating the presence or absence of devitrification. For example, in the case of "1050°C - 1078°C" described in the table, it means that devitrification occurred when heat treatment was performed at 1050°C, but devitrification did not occur in the treatment at 1078°C. In this case, the devitrification temperature is equal to or greater than 1050°C and less than 1078°C.
[0185] <Devitrification during simulated floatation cooling>
[0186] A cylindrical glass sample of about φ 20 mm x 15 mm was prepared from a glass block. The cylindrical glass sample was placed in a φ 40 mm crucible made of platinum-gold alloy, and heat treatment was performed in an electric furnace under conditions of simulated cooling of a floatation furnace, and then the sample was evaluated for the presence or absence of devitrification on the atmosphere side (hot forming side (fire forming side)) using an optical microscope. "N" in the table is a sample in which no devitrification was observed.
[0187] Note that, in order to make the glass viscosity η (unit: dPa-s) during cooling the same as that during floatation forming, the temperature was decreased to a temperature at which log η reached about 4.4 in 5 minutes from 1300°C, then decreased to a temperature at which log η reached about 5.5 in 25 minutes, then decreased to a temperature at which log η reached about 9.9 in 4 minutes, and then cooled at a cooling rate at which the glass did not break. Therefore, the temperature program during cooling varies depending on the glass composition. As an example, the temperature program in the case of the Al glass in Table 1 is shown in Figure 5
[0188] <Refractive index>
[0189] The refractive index was measured using a precision refractometer (manufactured by Shimadzu Corporation, KPR-2000) under d-rays (He light source, wavelength 587.6 nm).
[0190] <Photoelastic constant>
[0191] The circular plate compression method described in The American Ceramic Society Bulletin, Vol. 87 (1979), No. 1010, p. 519 was used for the measurement using a sodium lamp as a light source.
[0192] <Chemical strengthening properties>
[0193] The surface compressive stress CS1 and CS3 (unit: MPa), the compressive stress layer depth DOL1 and DOL3 (unit: μm) were measured using a measuring machine SLP1000 manufactured by Sakaguchi Seisakusho Co., Ltd. The surface compressive stress (CS2) (unit: MPa), the compressive stress layer depth (DOL2) (unit: μm) were measured using a surface stress meter FSM-6000 manufactured by Sakaguchi Seisakusho Co., Ltd.
[0194] Note that CS1 and DOL1 each represent the surface compressive stress and the compressive stress layer depth after one-step strengthening by immersing the obtained chemical strengthening glass in sodium nitrate at 450°C for 1 hour. CS2 and DOL2 each represent the surface compressive stress and the compressive stress layer depth generated through a Na-K ion exchange layer after two-step strengthening by immersing the obtained chemical strengthening glass in sodium nitrate at 450°C for 3 hours and then immersing in potassium nitrate at 450°C for 1.5 hours. Further, CS3 and DOL3 each represent the surface compressive stress and the compressive stress layer depth generated through a Li-Na ion exchange layer after two-step strengthening by immersing the obtained chemical strengthening glass in sodium nitrate at 450°C for 3 hours and then immersing in potassium nitrate at 450°C for 1.5 hours.
[0195]
[0196]
[0197]
[0198]
[0199] As can be seen, the glasses of Examples 1 to 23, 30 to 32, 37, in which the M value is 1000 or more, the I value is 600 or less, and the I2 value is 5 or less, have a large surface compressive stress CS1 generated by one-step strengthening, a large surface compressive stress CS2 generated by two-step strengthening, and a small crystal growth rate. With respect to these glass compositions, it is meant that in a batch production process such as a float method, it is difficult for devitrification defects to occur, a high yield can be expected, and a high strength can be exhibited in practical use of protective glass and the like.
[0200] As can be seen, Examples 33 to 36, which have M values of 1000 or more, I2 values of 5 or less, but slightly larger I values, have higher devitrification temperatures than Example 1, and are slightly easier to devitrify, but excellent strength is obtained by chemical strengthening.
[0201] As can be seen, although Examples 24, 26, and 27, which have M values of less than 1000 and small I and I2 values, sometimes have insufficient surface compressive stress produced by chemical strengthening, the crystal growth rate is small, and devitrification is not easy.
[0202] Example 25, which has a small M value and large I and I2 values, is a glass that has a large crystal growth rate and is difficult to manufacture.
[0203] The present application has been described in detail with particular reference to particular embodiments thereof, but it will be understood that various changes or modifications can be suggested to one skilled in the art, and it is intended that the application encompass such changes or modifications as fall within the spirit and scope of the application. This application is based on Japanese Patent Application (Japanese Patent Application No. 2018-018508) filed February 5, 2018, the contents of which are incorporated herein by reference.
[0204] Explanation of Symbols
[0205] 1 Platinum cell for devitrification evaluation
[0206] 2 Concave portion
[0207] 3 Glass particles
Claims
1. A chemically strengthened glass, wherein, The chemically strengthened glass, expressed as a molar percentage based on oxides, contains: 45%–68% SiO2, 11%–30% Al2O3, 1%–15% Li2O, 5%–10% Na2O, 0.5%–5% K2O, 1%–6% MgO, 0%~5% Y2O3, 0%–5% ZrO2, and 0%~1% TiO2, and Contains 1% to 20% of any one or more of MgO, CaO, SrO, BaO, and ZnO. The combined content of B2O3 and P2O5 is 0%–10%, and The value of M, expressed by the following formula, is greater than 1000 and less than 1350. M=-5×[SiO2]+121×[Al2O3]+50×[Li2O]-35×[Na2O]+32×[K2O]+85×[MgO]+54×[CaO]-41×[SrO]-4×[P2O5]+218×[Y2O3]+436×[ZrO2]-1180 Wherein, [SiO2], [Al2O3], [Li2O], [Na2O], [K2O], [MgO], [CaO], [SrO], [P2O5], [Y2O3], and [ZrO2] are the contents of each component expressed as molar percentages, and The value of I², expressed by the following formula, is greater than -1 and less than 3. I2=0.27×[SiO2]+1.4×[Al2O3]-1.1×[Na2O]-1.7×[K2O]+0.38×[MgO]-1.36×[Y2O3]-0.59×[ZrO2]-23 Wherein, [SiO2], [Al2O3], [Na2O], [K2O], [MgO], [Y2O3] and [ZrO2] are the contents of each component expressed as molar percentage.
2. The chemically strengthened glass as described in claim 1, wherein, The value of I, as expressed by the following formula, is below 600. I=-4.8×[SiO2]+102×[Al2O3]+81×[Li2O]-272×[Na2O]-281×[K2O]-16×[MgO]-25×[Y2O3]+0.028×[ZrO2]+63 Wherein, [SiO2], [Al2O3], [Li2O], [Na2O], [K2O], [MgO], [Y2O3] and [ZrO2] are the contents of each component expressed as molar percentage.
3. The chemically strengthened glass as described in claim 1 or 2, wherein, The ratio of [Li2O] / ([Na2O]+[K2O]) is 0.9 to 3.
4. The chemically strengthened glass as described in claim 1 or 2, wherein, The ratio of ([Al2O3]+[Li2O]) / ([Na2O]+[K2O]+[MgO]+[CaO]+[SrO]+[BaO]+[ZnO]+[ZrO2]+[Y2O3]) is greater than 0.7 and less than 4.
5. The chemically strengthened glass as described in claim 1 or 2, wherein, The viscosity of the chemically strengthened glass reaches 10. 4 The temperature (T4) at dPa·s is below 1350℃.
6. The chemically strengthened glass as described in claim 1 or 2, wherein, The surface compressive stress value of the chemically strengthened glass reaches over 300 MPa after being chemically strengthened by immersing it in sodium nitrate at 450°C for 1 hour. The surface compressive stress value of the chemically strengthened glass reaches more than 800 MPa after being immersed in sodium nitrate at 450°C for 3 hours and then in potassium nitrate at 450°C for 1.5 hours.
7. The chemically strengthened glass as described in claim 1 or 2, wherein, The chemically strengthened glass has a Young's modulus of 80 GPa or higher.
8. A chemically strengthened glass, wherein, The basic composition of the chemically strengthened glass, expressed as a molar percentage based on oxides, contains: 45%–68% SiO2, 1%–30% Al2O3, 1%–20% Li2O, 5%–10% Na2O, 0.5%–5% K2O, 1%–6% MgO, 0%~5% Y2O3, 0%–5% ZrO2, and 0%~1% TiO2, and Contains 1% to 20% of any one or more of MgO, CaO, SrO, BaO, and ZnO. The combined content of B2O3 and P2O5 is 0%–10%, and The value of M, expressed by the following formula, is greater than 1000 and less than 1350. M=-5×[SiO2]+121×[Al2O3]+50×[Li2O]-35×[Na2O]+32×[K2O]+85×[MgO]+54×[CaO]-41×[SrO]-4×[P2O5]+218×[Y2O3]+436×[ZrO2]-1180 Wherein, [SiO2], [Al2O3], [Li2O], [Na2O], [K2O], [MgO], [CaO], [SrO], [P2O5], [Y2O3], and [ZrO2] are the contents of each component expressed as molar percentages, and The value of I², expressed by the following formula, is greater than -1 and less than 3. I2=0.27×[SiO2]+1.4×[Al2O3]-1.1×[Na2O]-1.7×[K2O]+0.38×[MgO]-1.36×[Y2O3]-0.59×[ZrO2]-23 Wherein, [SiO2], [Al2O3], [Na2O], [K2O], [MgO], [Y2O3] and [ZrO2] are the contents of each component expressed as molar percentage.
9. The chemically strengthened glass as described in claim 8, wherein, The value of I, as expressed by the following formula, is below 600. I=-4.8×[SiO2]+102×[Al2O3]+81×[Li2O]-272×[Na2O]-281×[K2O]-16×[MgO]-25×[Y2O3]+0.028×[ZrO2]+63 Wherein, [SiO2], [Al2O3], [Li2O], [Na2O], [K2O], [MgO], [Y2O3] and [ZrO2] are the contents of each component expressed as molar percentage.
10. The chemically strengthened glass as described in claim 8 or 9, wherein, The ratio of [Li2O] / ([Na2O]+[K2O]) is 0.9 to 3.
11. The chemically strengthened glass as described in claim 8 or 9, wherein, ([Al2O3]+[Li2O]) / ([Na2O]+[K2O]+[MgO]+[CaO]+[SrO]+[BaO]+[ZnO]+ The concentration of [ZrO2]+[Y2O3]) is above 0.7 and below 4.
12. The chemically strengthened glass as described in claim 8 or 9, wherein, The surface compressive stress value of the chemically strengthened glass is above 800 MPa.
Citation Information
Patent Citations
Chemically strengthened glass
JP2013520388A
Un ALM total management system derived from travel-associated real estate commodities for proving wealthy and gentle lives to all people on earth
JP2018018508A
Strengthened glass with deep depth of compression
US20150259244A1